The role of qard accounting in sharia insurance of the covid-19 period - Nano Suyatna (Jurnal Mantik, 2023)
The Covid-19 pandemic is a massive phenomenon disrupting all activities, including the insurance business soul of sharia. Where sharia life insurance is a competitive and high-risk trust business, because it is transacted in the future. Efforts to maintain business continuity are very necessary. The aim of this research is to determine the role of qardh accounting in taking over financial risks in this case maintaining the Solvency level of the Tabarru Fund so that it remains considered financially healthy. The research method used is a descriptive method and data analysis. The collected data is visualized in the form of graphs and tables so that it is easy to understand the meaning. The research results show that there is a role for qardh accounting in maintaining the solvency level of tabarru' funds, so that sharia life insurance companies avoid sanctions from the Financial Services Authority and failure to pay. During the Covid-19 Pandemic, there were no defaults compared to conventional insurance.